The Analysis of Factors Affecting Income Level of Street Vendors - Indah Setyaningsih; Sukiman Sukiman; Neni Widyaningsih (EKO-REGIONAL, 2019)
This study aimed to analyze the income level of the family of street vendors obtained from selling foods and beverages at tourist attraction of Suwuk Beach, Kebumen Regency. This study analyzed the relationship between business initial capital, education level, gender, length of business, and number of workers with income of street vendors. This study used data obtained from 53 respondents. The analytical tool used Cross-section analysis. The estimation results indicated that business initial capital, number of workers, and length of business had a significant effect on the business income. While gender and education level did not have a significant effect on the business income.